Learning through metaverse: exploring the role of virtual reality to enhance English language proficiency / Stefanie Natasha Rich Joseph ... [et al.] - Rich Joseph, Stefanie Natasha; Doubless John, Daryl Albright; Robert, Cindy; Jafri, Fakhira; Ajol, Tracy Adeline (Universiti Teknologi MARA, Kedah, 2023)
Conventional English language pedagogy falls short in offering immersive and engaging learning environments for students, both of which are required for growing English language competency. Virtual reality (VR) has emerged as a potentially useful tool in the domain of language learning, offering students a unique and comprehensive educational experience with the potential to improve language competency through customised instructional methods. In this study, the benefits of immersive virtual reality simulation; using the platform Metaverse; on English language acquisition for language proficiency enhancement were assessed using a mixed-methods approach. Data was collected through surveys, interviews, and classroom observation which were then evaluated using a descriptive approach of frequency counts, averages, and percentages. The research transcriptions wereused to determine students' motivation for Second Language Acquisition (SLA) outside of conventional classroom instruction and its impact in enhancing English language proficiency. Despite the obstacles the researchers found in implementing virtual reality simulations in educational settings, the research results showed an increase in performance, motivation, and language acquisition. The findings of this study contribute to the current body of literature on the use of virtual reality technology in educational settings and its potential for creating customised virtual reality content. The limitations of conventional language learning methods and the need for innovative approaches to boost language proficiency is also highlighted. Further investigation and advancement in the field of virtual reality are necessary to comprehensively examine its potential in language education and evaluate its influence on learners' language proficiency and multilingual abilities.